2016
DOI: 10.1177/0146621616665196
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Response Distribution–Based Item Selection Algorithms for Short-Length Cognitive Diagnostic Computerized Adaptive Testing

Abstract: Cognitive diagnostic computerized adaptive testing (CD-CAT) purports to obtain useful diagnostic information with great efficiency brought by CAT technology. Most of the existing CD-CAT item selection algorithms are evaluated when test length is fixed and relatively long, but some applications of CD-CAT, such as in interim assessment, require to obtain the cognitive pattern with a short test. The mutual information (MI) algorithm proposed by Wang is the first endeavor to accommodate this need. To reduce the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Cheng (2010) used KL information method to select items successively, whereas many studies have demonstrated that PWKL information method performed better than KL information method in terms of pattern and ACCR (Cheng, 2009a,b;Mao and Xin, 2013;Wang, 2013;Hsu and Wang, 2015;Zheng and Chang, 2016). And the MPWKL information method may perform even better than PWKL (Kaplan et al, 2015).…”
Section: Item Selection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng (2010) used KL information method to select items successively, whereas many studies have demonstrated that PWKL information method performed better than KL information method in terms of pattern and ACCR (Cheng, 2009a,b;Mao and Xin, 2013;Wang, 2013;Hsu and Wang, 2015;Zheng and Chang, 2016). And the MPWKL information method may perform even better than PWKL (Kaplan et al, 2015).…”
Section: Item Selection Methodsmentioning
confidence: 99%
“…As a consequence, cognitive diagnostic tests would be conducted more frequently than traditional tests in some areas such as interim assessment (Roussos et al, 2007;Hartz and Roussos, 2008;Mao and Xin, 2013;Kaplan et al, 2015). When CD-CAT is applied to interim assessment, the AMPs of students should be obtained with shortlength tests (Zheng and Chang, 2016). Second, to the best of our knowledge, among the studies focused on short-length test, there are only two applied that CD-CAT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some situations, the opposite effects were observed for these item-selection methods. For example, when a short test was used (fewer than 10 items), the Shannon entropy method and its modified approach of the mutual information method were found to be more efficient than the PWKL method in terms of the attribute mastery classification in CD-CAT (Wang, 2013;Zheng & Chang, 2016). The PWKL method was derived based on the KL information measure to quantify the distance or discrepancy between two probability distributions.…”
Section: Cd-cat Algorithmsmentioning
confidence: 99%
“…Tatsuoka & Ferguson, 2003;Xu et al, 2003), the likelihood-or posterior-weighted KL (LWKL or PWKL) index and the hybrid KL index (Cheng, 2009), the restrictive progressive or threshold PWKL index (Wang et al, 2011), the aggregate ranked information index and the aggregate standardized information index (Wang et al, 2014), the modified PWKL (MPWKL) index (Kaplan et al, 2015), the KL expected discrimination index (W. Y. Wang et al, 2015), the posterior-weighted cognitive diagnostic model (CDM) discrimination index and the posteriorweighted attribute-level CDM discrimination index (Zheng & Chang, 2016), and the information product index (Zheng et al, 2018). The second is based on the Shannon entropy, called the Shannon entropy (SHE) procedure (Cheng, 2009;McGlohen & Chang, 2008;C.…”
mentioning
confidence: 99%